On Dissemination of the Catholic Social Ideas in Lithuania - Pruskus, Valdas (Problemos, 1996)
The views of Lithuanian patriotic clergy on cooperation are discussed (J. Dabušis, S. Šultė, J. Vailokaitis, F. Kemėšis, M. Krupavičius, etc.). They believed that the cooperation is not only a defensive measure for a nation as an economic subject against the predatory capitalism associated with the foreign businessmen activities in Lithuania. It is also a non-compulsive way of organizing the more equitable society. Propagating the cooperation ideas in various strata of society, organizing them in cooperative systems, clergy has been seeking to arouse an initiative in people, their sense of duty and responsibility. They stimulated considerably the formation of the working class and of the peasantry and their professional improvement. In that way Lithuania could, after proclaiming independence in 1918, in spite of destructive consequences of the World War I, to restore and develop own economy in a comparatively short period.